Pelatihan Asistensi Artificial Intelligence (AI) terkait penulisan Bahasa Inggris pada PT. KCI Indonesia - Dinanti, Putri Ayienda; Sibuea, Todo (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
The Artificial Intelligence (AI) Assistance Training for English writing at PT. KCI Indonesia is designed to address the written communication challenges faced by employees. This program aims to enhance English writing skills by utilizing AI technology that provides real-time feedback on grammar, vocabulary, sentence structure, and giving ideas to write. In the era of globalization, strong written communication skills have become essential to ensure professionalism in various business documents. Furthermore, this training is designed to support employees in drafting documents that align with the needs of the business context. The program's implementation methods include socialization, training, mentoring, and performance evaluation. The training results indicate improvements in employees' writing skills, making them more efficient. Employees have become more confident in preparing various types of business documents. The company's employees are now better equipped to enhance English literacy within the business context. With an innovative AI-based approach, this program offers a relevant solution for PT. KCI to face future global challenges